Analysis of Energy Performance of Institutional Buildings in Subtropical Climate. (March 2017) - Chowdhury, Ashfaque Ahmed; Rasul, M.G.; Khan, M.M.K.
Abstract: Energy analysis and assessment are required to identify how much, where and how energy is used within a facility. The purpose is to analyse and assess the energy consumption pattern through the analysis of the historical energy consumption data by the buildings in an academic institution located in the subtropical region of Australia. This study reports some of the findings from the survey of the institutional buildings and the measurements of the energy consumption data related to the internal thermal load. The monthly monitored energy usages of the buildings are used to analyse the effects of climatic variation on energy utilization. The distinctiveness of this study is that the developed correlations between the energy utilization and weather pattern can be used to plan the sustainable operation of the institutional buildings in the subtropical region. Most importantly, the increased energy consumption pattern in the buildings will provide a good indication of the design feature and energy efficiency requirements in the building located in this climate.